Damage of the medial preoptic area impairs peripheral pilocarpine-induced salivary secretion - de Almeida, R. L.; De Luca, L. A.; Colombari, DSD; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP] (Elsevier B.V., 2006)
The existence of neural connections between the medial preoptic area (MPOA) and the salivary glands and the increase in salivation by thermal or electrical stimulation of the MPOA have suggested an important role of MPOA in the control of salivary gland function. Although direct cholinergic activation of the salivary glands induces salivation, recent studies have suggested that salivation produced by i.p. pilocarpine may also depend on the activation of central mechanisms. Therefore, in the present study, we investigated the effects of bilateral electrolytic lesions of the MPOA on the salivation induced by i.p. pilocarpine. Adult male Holtzman rats (n = 11-12/group) with bilateral sham or electrolytic lesions of the MPOA were used. One, five, and fifteen days after the brain surgery, under ketamine anesthesia, the salivation was induced by i.p. pilocarpine (1 mg/kg of body weight), and saliva was collected using preweighted small cotton balls inserted into the animal's mouth. Pilocarpine-induced salivation was reduced 1 and 5 days after MPOA lesion (341 +/- 41 and 310 +/- 35 mg/7 min, respectively, vs. sham lesions 428 +/- 32 and 495 +/- 36 mg/7 min, respectively), but it was fully recovered at the 15th day post-lesion (561 +/- 49 vs. sham lesion: 618 27 mg/7 min). Lesions of the MPOA did not affect baseline non-stimulated salivary secretion. The results confirm the importance of MPOA in the control of salivation and suggest that its integrity is necessary for the full sialogogue effect of pilocarpine. However, alternative mechanisms probably involving other central nuclei can replace MPOA function in chronically lesioned rats allowing the complete recovery of the effects of pilocarpine. (c) 2006 Published by Elsevier B.V.
Keywords: salivation; cholinergic receptor; preoptic area; salivary gland; parasympathetic; brain plasticity